2019
DOI: 10.1111/pbi.13127
|View full text |Cite
|
Sign up to set email alerts
|

Drought‐responsive genes, late embryogenesis abundant group3 (LEA3) and vicinal oxygen chelate, function in lipid accumulation in Brassica napus and Arabidopsis mainly via enhancing photosynthetic efficiency and reducing ROS

Abstract: Summary Drought is an abiotic stress that affects plant growth, and lipids are the main economic factor in the agricultural production of oil crops. However, the molecular mechanisms of drought response function in lipid metabolism remain little known. In this study, overexpression (OE) of different copies of the drought response genes LEA3 and VOC enhanced both drought tolerance and oil content in Brassica napus and Arabidopsis. Meanwhile, seed size, membrane stability and seed weight were also improved in OE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
79
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(83 citation statements)
references
References 78 publications
(106 reference statements)
3
79
0
1
Order By: Relevance
“…However, the use of low marker density genetic linkage map was not able to reveal the comprehensive genetic diversity of drought tolerance in rapeseed ( Li et al, 2014 ). Despite the progress made in the plant’s response to drought stress, many genetic bases of drought tolerance in rapeseed has yet to be clarified ( Li et al, 2014 ; Zhang, 2015 ; Zhao et al, 2016 ; Liang et al, 2019 ). There has been significant progress in understanding the signaling process that controls plant resistance to drought from perception of signals to cellular mechanisms ( Seki et al, 2007 ), and it was revealed that the signal pathways including many common factors, such as abscisic acid, photosynthesis, and reducing ROS contents under drought, were involved in drought resistance ( Jackson et al, 2003 ; Li et al, 2006 ; Dudziak et al, 2019 ; Liang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of low marker density genetic linkage map was not able to reveal the comprehensive genetic diversity of drought tolerance in rapeseed ( Li et al, 2014 ). Despite the progress made in the plant’s response to drought stress, many genetic bases of drought tolerance in rapeseed has yet to be clarified ( Li et al, 2014 ; Zhang, 2015 ; Zhao et al, 2016 ; Liang et al, 2019 ). There has been significant progress in understanding the signaling process that controls plant resistance to drought from perception of signals to cellular mechanisms ( Seki et al, 2007 ), and it was revealed that the signal pathways including many common factors, such as abscisic acid, photosynthesis, and reducing ROS contents under drought, were involved in drought resistance ( Jackson et al, 2003 ; Li et al, 2006 ; Dudziak et al, 2019 ; Liang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, searching for LEAinteractive proteins is important in future studies. Additionally, LEA proteins can segregate harmful metal ions and ROS to reduce their damaging effects under stress conditions [11,12,15,32] . As shown in this study, ROS accumulation in PtrLEA7 overexpressed plants was significantly reduced (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For example, overexpressing OsLEA3-1 in rice can confer enhanced drought tolerance without reducing yield [10] . The LEA3 gene from Brassica napus was identified to be a positive regulator of drought tolerance by reducing reactive oxygen species (ROS) accumulation and enhancing photosynthetic efficiency [11] . ZmLEA3 from maize can confer enhanced low temperature and osmotic stress tolerance by protecting lactate dehydrogenase activity and binding metal ions [12,13] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations